2017
DOI: 10.3390/en10040577
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison between Selected Evaporative Air Coolers

Abstract: Abstract:The aim of this study is to determine which of the heat exchangers is characterized by the highest efficiency in different applications. Various types of evaporative air coolers were compared: a typical counter-flow unit, the same unit operating as a heat recovery exchanger, a regenerative unit and a novel, modified regenerative exchanger. The analysis includes comparing the work of evaporative heat exchangers during summer and winter season. The analysis is based on the original mathematical models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…An increase in humidity level causes discomfort and it is the key limitation of the DEC system [12][13][14]. Indirect evaporative cooling is a constant humidity process in which ambient air temperature decreases without the addition of moisture/humidity in the air [15,16]. In this process, the air is not directly in contact with water.…”
Section: Proposed Evaporative Cooling (Ec) Optionsmentioning
confidence: 99%
“…An increase in humidity level causes discomfort and it is the key limitation of the DEC system [12][13][14]. Indirect evaporative cooling is a constant humidity process in which ambient air temperature decreases without the addition of moisture/humidity in the air [15,16]. In this process, the air is not directly in contact with water.…”
Section: Proposed Evaporative Cooling (Ec) Optionsmentioning
confidence: 99%
“…Moreover using the product channel allows reducing pressure drop in the system. Another advantage of arrangement in Figure 1 (b) compared with Figure 1a would be a possibility to use the product channel as a condenser for gas dehumidification [4].…”
Section: Fundamentals Of M-cycle Hmxmentioning
confidence: 99%
“…Zhan et al [15], Anisimov et al [16], and Pandelidis et al [17] each provided a comparative study of different configurations of HMXs. Their results have shown that a counter-flow HMX offers high cooling effectiveness but yields lower values of cooling capacity to handle a large cooling load.…”
Section: Introductionmentioning
confidence: 99%